Analisa Harmonisa Pada Base Tranciever Station (BTS) Di Gedung Prodi Teknik Mesin Fakultas Teknik Universitas Kristen Indonesia (UKI) – Jakarta - FILIP DONATAL Filip; Eva Magdalena Silalahi; Robinson Purba (Prodi Teknik Elektro FT UKI, 2023)
The current development of telecommunications technology has reached 4G LTE technology, and some have even implemented 5G technology. One of the infrastructures that supports the advancement of telecommunication technology is the BTS. Components in BTS include, rectifier, microwave link, BTS radio equipment, air conditioner (AC). This component belongs to the category of nonlinear electrical loads which cause harmonic problems in BTS. Therefore, it is necessary to measure the harmonic level at each BTS for a study that includes the level of voltage and current harmonic distortion due to nonlinear components in BTS including BTS in the Mechanical Engineering Study Program Laboratory Building, Faculty of Engineering, UKI Jakarta. Based on the harmonic measurements carried out on this BTS, the results obtained are: BTS has a total current distortion value, THDi of 10.16% which exceeds the IEEE 519-2014 standard. The total value of voltage distortion, THDv is 1.11%, which still meets the IEEE 519-2014 standard. The dominant THDi value in BTS occurs in the 3rd order with a THDi of 8.7% and the 5th order with a THDi of 4.2% exceeding the 4% limit of the IEEE 519-2014 standard.